Gender differences in patterns of relationship between body mass index and AF incidence. (25th November 2020) - Senoo, K; Nakata, M; Teramukai, S; Yamamoto, T; Nishimura, H; Matoba, S
Abstract: Background: Obesity is reportedly associated with the new incidence of atrial fibrillation (AF). However, gender differences in patterns of relationship between body mass index (BMI) and the risk of AF are unknown. Methods: We analyzed 21, 382 middle-aged Japanese subjects (10923 men, 10459 women) without AF from a cohort of employees undergoing annual health examinations, with a follow-up period of 4.8±3.7 years. We examined the relationship between BMI at baseline to AF incidence in unadjusted and adjusted analyses. This relationship was also studied using linear and quadratic models. Results: AF had developed in 137 subjects (119 men; mean age, 54.4±8.2 years; incidence, 2.19 and 0.38 per 1000 person-years in men and women, respectively). In multivariable Cox proportional-hazard models, increasing age (hazard ratio [HR], 2.72 per year; 95% CI, 2.22 to 3.33; P<0.001), male gender (HR, 3.28; 95% CI, 1.86 to 5.76; P<0.001) and BMI (HR, 1.08; 95% CI, 1.02 to 1.15; P=0.007) were associated with the new incidence of AF in all cohorts. The shape of the BMI-incident AF relationship showed a linear association in women and a J-shaped association in men. (Figure) In particular, a U-shaped relationship was observed in young men aged 40–49, with increased risk among those with higher BMI and with very low BMI. In analyses adjusted for comorbidities and risk factors for CV disease, the U-shaped AF incidence versus BMI curves were not attenuated, suggesting that other genetic or congenital factors may mediate this relationship. Conclusion: Our results indicate that the shape of the BMI-incident AF relation differs by sex and in particular a U-shaped relationship was observed in young men. Funding Acknowledgement: Type of funding source: None